Madchenseele - Scheschonk, Anne (Germany, 2017)
It's quite clear to 7-year old Nori: she is a girl because she has a girl's heart, but her body is that of a boy. For five years, mother and son argued about his appearance. The neighbors start gossiping. Then one day, the boy reveals to his mother that he wants a wizard to turn his penis into a vagina so he could be a “real” girl. Josephin realizes that she doesn’t have a son, that he never existed – but that there is still a child, a daughter. It becomes clear that she will have to break new ground to see her daughter grow up happy. The documentary portrays the conflict young Nori and her mother face in trying to enable a life worth living outside of the norm. A film about being a girl.
Keywords: Documentary films